Variability between human experts and artificial intelligence in identification of anatomical structures by ultrasound in regional anaesthesia: a framework for evaluation of assistive artificial intelligence - Bowness, JS; Morse, R; Lewis, O; Lloyd, J; Burckett-St Laurent, D; Bellew, B; Macfarlane, AJR; Pawa, A; Taylor, A; Noble, JA; Higham, H (Elsevier, 2023)
Background: ScanNavTM Anatomy Peripheral Nerve Block (ScanNav™) is an artificial intelligence (AI)-based device that produces a colour overlay on real-time B-mode ultrasound to highlight key anatomical structures for regional anaesthesia. This study compares consistency of identification of sono-anatomical structures between expert ultrasonographers and ScanNav™.